Phytochemicals, Nutritional and Elemental Composition of different plant parts of Rinorea oblongifolia (C.H Wright) C. Marquand ex Chipp - Adeniyi Ohunayo; Olusola Elekofehinti; Muftau Kolawole Oladunmoye; Anthony Kayode Onifade (Kashmir Journal of Science)
Antioxidants are essential in managing chronic diseases by neutralizing free radicals and reducing oxidative stress. Rinorea oblongifolia, a medicinal plant, contains a rich profile of phytochemicals and minerals, adding to its therapeutic potential. This study provides a detailed analysis of the proximate, phytochemical, mineral, and antioxidant properties of its leaves, stems, and roots. The plant parts were collected, air-dried, and ground into powder for evaluation. Phytochemical screening detected alkaloids, saponins, tannins, phenolics, flavonoids, steroids, and terpenoids, with the highest concentrations in the leaves. Proximate analysis showed that the leaves had the highest moisture (9.17%), crude protein (9.91%), and carbohydrate (75.26%) contents, while roots had the highest ash (2.45%) and crude fat (4.61%). Mineral analysis showed that the roots were rich in iron, calcium, and copper, while leaves contained more potassium, sodium, phosphorus, and magnesium. Antioxidant assays (DPPH, FRAP, ABTS) revealed significant free radical scavenging, especially in the leaves. These findings support oblongifolia’s potential for nutritional supplements and therapeutic uses, with further research needed to investigate mechanisms and standardize extraction protocols.